(untitled) (American Journal of Arts and Human Science, 2025)
This study explores the prevalent miscarriages of justice within Nigerian society and the resultant erosion of confidence in the Nigerian justice system, often perceived as flawed. This lack of trust fosters fear and drives individuals to make desperate, sometimes harmful, decisions. Although achieving true justice may seem like a distant goal, it becomes more attainable through collective action, emphasizing the power of unity. Theatre, as a potent medium accessible to diverse audiences, serves as an effective catalyst for justice, fostering awareness, empowerment, and potential societal transformation. Through a literary lens, this study analyzes three plays; Osita Ezenwanebe’s Withered Thrust, Akachi Ezeigbo’s Hands that Crush Stone, and Femi Osofisan’s Morountodun—to demonstrate how communal efforts can triumph over individual struggles in the pursuit of justice. The findings reveal that collective action empowers communities and fosters justice for individuals. This research highlights the intersection of theatre and social change, illustrating how artistic expression can inspire collective efforts for justice.